Perspectives of people living with HIV age 50 and over regarding barriers and resources for care. Issue 4 (3rd April 2023) - Davis, Amelia J.; Greene, Meredith; Walker, Jacob; Erlandson, Kristine M.
ABSTRACT : With early and effective antiretroviral therapy leading to improved life expectancy in people with HIV (PWH), PWH aged 50 or older face concerns and issues related to aging. Providers at the University of Colorado identified a need to assess the healthcare needs of PWH aged 50 and older at the UCHealth Infectious Diseases/Travel (TEAM) Clinic in Aurora, Colorado. A survey was developed to illuminate participants' general rating of their health, factors that made it challenging to get the healthcare needed prior to COVID-19 and during COVID-19, and types of healthcare appointments and providers that would make a difference in healthcare experience. Descriptive statistics and brief thematic analysis of open-ended questions found that most participants rated their current health as very good or good. Participants noted that connecting to resources and appointment scheduling were the top challenges prior to the COVID-19 pandemic, and during the COVID-19 pandemic, participants described challenges with resource connection, communication with providers, and wait times. To reduce these barriers, telehealth video appointments, healthcare visits with a provider who specializes in aging, and healthcare visits with providers who specialize in aging if co-located in the HIV clinic were recognized as beneficial resources from the perspectives of participants.